Palisaded Neutrophilic and Granulomatous Dermatitis in a Patient with Granulomatosis with Polyangiitis - Mai Akagawa; Yuki Hattori; Yoko Mizutani; En Shu; Tatsuhiko Miyazaki; Mariko Seishima (Karger Publishers, 2020)
Palisaded neutrophilic and granulomatous dermatitis (PNGD) shows various clinical features and is histologically characterized by palisaded granulomas surrounding degenerated collagen. PNGD is known to be associated with a variety of systemic conditions such as rheumatoid arthritis and systemic lupus erythematosus. Furthermore, PNGD has been reported to be associated with antineutrophilic cytoplasmic antibody-associated vasculitis, including granulomatosis with polyangiitis (GPA) and microscopic polyangiitis. Here, we report a case of PNGD associated with GPA, which showed the infiltration of CD163-positive M2 macrophages in the skin lesion with elevated serum level of soluble CD163 (sCD163). The serum sCD163 level was reduced to normal range after systemic steroid therapy. Thus, M2 macrophages may play a role in the pathomechanisms of PNGD associated with GPA.